2020
DOI: 10.3390/pathogens9020128
|View full text |Cite
|
Sign up to set email alerts
|

Will Nigerians Win the War Against Urinary Schistosomiasis? Prevalence, Intensity, Risk Factors and Knowledge Assessment among Some Rural Communities in Southwestern Nigeria

Abstract: Urinary schistosomiasis is a devastating parasitic disease in Nigeria. This study was carried out to investigate the current prevalence, intensity, risk factors and knowledge assessment among some rural communities in southwestern Nigeria. A cross-sectional study was carried out in which a standard urine filtrations technique was used to determine the prevalence and intensity of infection. A well-designed questionnaire was used to collect subject’s data on demographic and socioeconomic characteristics. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
2
12
1
Order By: Relevance
“…These communities depend on the dam for their domestic water supply, fishing, and other water-related activities. There have been previous reports of schistosome endemicity in these communities [25].…”
Section: Study Sitementioning
confidence: 86%
See 1 more Smart Citation
“…These communities depend on the dam for their domestic water supply, fishing, and other water-related activities. There have been previous reports of schistosome endemicity in these communities [25].…”
Section: Study Sitementioning
confidence: 86%
“…The sample size was obtained using the formula for a cross-sectional study [26]. Using a prior prevalence of 37.5% among school children positive for schistosomiasis [25],a marginal error of 5%, and a type 1 error of 5%, a minimum sample of 289 school children was needed.…”
Section: Study Design and Sample Size Calculationmentioning
confidence: 99%
“…S2 Table provides the overall quality score for each study included in the review. Only 33 (around 25%) of the included studies met the threshold for high quality with eight studies obtaining the highest scores of 9/9 [22][23][24][25][26][27][28][29]. 85 studies were found to be of moderate quality.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…This was attributed to snail abundance in temporary water bodies in both studies. Amongst the studies that report a significantly higher prevalence of infection in males, 16 studies [22,38,40,41,43,50,[55][56][57][58][59][60][61][62][63][64], attribute this difference to gender-specific water-contact activities in which males tend to have more frequent water contact either because of cultural or religious beliefs, occupational reasons, or social roles.…”
Section: Summary Of Identified Risk Factorsmentioning
confidence: 99%
“…The name is derived from haematuria (bloody urine), which serves as the classical sign of the disease (Atalabi & Adubi, 2018). For decades, urinary schistosomiasis has ravaged Nigerian communities, parasitizing local dwellers and inflicting severe morbidity and disabilities among affected populations (Awosolu et al, 2020). Being an infectious disease of poverty, it disproportionately afflicts poor and marginalized communities, predisposing the affected population to a greater risk of human immune virus (HIV) and cancer, prolonging the course of enterobacterial infections and eliciting antimicrobial resistance (Awosolu et al, 2020;Mohamed et al, 2019;Wall et al, 2019;Hsiao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%